Formation of Mining Districts in the End of 18th - First Half of 19th Century on Territory of Modern Udmurtia - T. A. Vasina (Tsentr nauchnykh i obrazovatelnykh proektov, 2019)
Features of formation and development of mining districts in the territory relating to modern Udmurtia in the pre-reform period (the end of the 18th - the first half of the 19th century) are considered. The study is based on archival materials, publications in Vyatskie Gubernskie Vedomosti , as well as on the historiographical tradition, in particular, the works of historians of the Urals, devoted to the concept of “mining district.” The focus is on the history of the founding of metallurgical enterprises: Pudem Ironworks, Kamsko-Votkinsk Ironworks, Izhevsk Arms Factory and Ironworks, Bemyshev Copper Works, their productivity. The complex of natural factors that influenced the choice of places for the construction of plants is characterized. It is shown that the main resource base of the mining industry were local ore deposits, reservoirs (rivers and ponds with dams), forests, as well as human resources. It is concluded that the mining districts in the study area, formed in the process of extensive development of the mining industry of the Urals, were complexly organized territorial socio-economic complexes with a multi-layered system of economy, they included various types of land, villages of peasants and other categories of workers, kurens, cutting areas, mines, marinas, etc., located on a large territory.